Analysis of the accidents related to container losses at sea - Seah, Priscilla Xinzhen (Nanyang Technological University, 2024)
This report focuses on three key objectives: compiling and comparing ship resistance data from various authors, formulating an equation to compute the wake fraction using relevant variables, and generating the shortest possible route between two port locations.